The impact of sensory modalities and background information on the emotional resonance of Li Bai’s classical poetry - Zhang, Yannan; Wang, Xiao (Frontiers in Psychology, 2025)
IntroductionEmotional resonance (ER) refers to the extent to which readers identify with and emotionally connect to the representations in poetry, often drawing parallels between the emotions conveyed in the poem and their own personal experiences. This phenomenon is influenced by sensory modalities—such as visual, auditory, tactile, gustatory, and olfactory—and the cultural context embedded within the poem. Understanding how these factors interact to enhance emotional resonance in poetry is crucial for advancing poetry education and engagement.MethodsThis study employs a repeated-measures experimental design to investigate how different sensory modalities and contextual background influence emotional responses to classical poetry. The experiment includes five conditions: three focus on sensory modalities (visual, auditory, and visual-auditory), while the remaining two examine the combined effects of background information (background music and background images) in conjunction with sensory modalities.ResultsThe results indicate that: The visual modality and the visual-auditory modality yield higher emotional resonance ratings compared to the auditory modality. Background information (background music and images) enhances the emotional resonance of the poetry. The synergy between background information and sensory modalities further increases the emotional resonance ratings.DiscussionThis study highlights the critical role of both sensory modalities and background information in shaping the emotional response to poetry. The findings suggest that integrating different sensory experiences and cultural cues can significantly enhance emotional resonance, offering new theoretical insights for the teaching and appreciation of poetry.